Antibiotic treatment duration and prevention of complications in neonatal Staphylococcus aureus bacteraemia. Issue 2 (October 2015) - Kempley, S.; Kapellou, O.; McWilliams, A.; Banerjee, J.; McCorqodale, A.; Millar, M.
Summary Background In adults with Staphylococcus aureus bacteraemia, short duration of effective antibiotic treatment is associated with increased risk of complications and recurrence. The optimum duration of treatment for neonates is unknown and practice varies widely. Aim To relate the duration of treatment of neonatal S. aureus bacteraemia to prevention of complications and recurrence. Methods Retrospective cohort study of confirmed S. aureus bacteraemia occurring over a 10 year period in two large tertiary neonatal units. Neonatal patients developing confirmed S. aureus bacteraemia between birth and discharge from the neonatal unit were identified from microbiology department records. Clinical details obtained from case notes included demographics, duration of antibiotics and clinical outcomes. Recurrence was determined from laboratory and clinical records. Adverse outcomes were related to duration of antibiotic therapy. Findings A total of 90 infants had S. aureus bacteraemia, of which six were meticillin-resistant S. aureus (7%). Median gestation was 27 weeks (range: 23–41), birth weight 846 g (434–3840) and postnatal age 16 days (0–116). Adverse outcomes were found in 44%, with death in 8%. Median duration of appropriate antibiotics was 19 days (range: 0–54). There were no cases of recurrent bacteraemia after finishing antibiotics. There was no relationship between antibiotic duration and complications. Conclusion Neonatal S. aureus bacteraemia mainly affected preterm neonates and had a significant morbidity and mortality. Recurrent bacteraemia was rare, irrespective of treatment duration. For neonatal unit patients with S. aureus bacteraemia, antibiotic therapy for 14 days in uncomplicated cases may be sufficient to prevent recurrence, with longer treatment justified if there is inadequate source control.